Self-Rotating Spherical Evaporator Based on Hydrogel and Black Titanium Oxide for Continuous Desalination of Seawater - Ge, Yumeng; Su, Zewen; Wang, Le; Wang, Congcong; Cai, Peiqing; Lin, Shenghuang; Liu, Yuan; Xu, Shiqing; Bai, Gongxun (ACS materials letters, 2023)
Solar interfacial water evaporation technology has shown great promise for seawater desalination and wastewater treatment. However, the deposition of salt crystals on the evaporator surface restrains the evaporation rate, which will affect further development of this technology. In this work, a spherical polystyrene foam was utilized as the material support, the surface of which was coated with photothermal materials for evaporator fabrication. The employing of well-prepared black Ti4O7 as a photothermal coating greatly improve the sunlight absorption of the surface, and the mixing of sodium alginate can achieve a hydrophilic effect. This unique coordination not only increases the evaporation rate of the spherical evaporator (2.46 kg m–2 h–1), but also performs well in water purification. The spherical design allows the evaporator to periodically clean the salt deposits on the evaporator surface through self-rotation, which provides a promising way to deal with the problem of salt deposition in evaporators in the future.